2015
DOI: 10.2174/1389203716666150330141922
|View full text |Cite
|
Sign up to set email alerts
|

The Common Molecular Players in Plant Hormone Crosstalk and Signaling

Abstract: Plant growth and development is under the control of mutual interactions among plant hormones. The five classical categories of plant hormones include auxins, cytokinins, gibberellins, abscisic acid and ethylene. Additionally, newer classes of plant hormones have been recognized like brassinosteroids, jasmonic acid, salicylic acid and polyamines. These hormones play significant roles in regulating the plant growth and development. Various receptors and key signaling components of these hormones have been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Some reports revealed that the metabolite composition was affected by the cumulative action of both SA and BR (24-epibrassinolide) leading to a decline in lead toxicity (Kohli et al, 2018). The interplay between BR and SA may be due to the NPR1 gene (non-expressor of pathogenesisrelated genes 1) which stimulates expression of the SA-related genes involved in plant defense (Ohri et al, 2015). NPR1 also regulates the BR signaling genes, BIN2 and BZRI, which induces stress tolerance in plants (Divi et al, 2010).…”
Section: Brassinosteroids and Salicylic Acidmentioning
confidence: 99%
“…Some reports revealed that the metabolite composition was affected by the cumulative action of both SA and BR (24-epibrassinolide) leading to a decline in lead toxicity (Kohli et al, 2018). The interplay between BR and SA may be due to the NPR1 gene (non-expressor of pathogenesisrelated genes 1) which stimulates expression of the SA-related genes involved in plant defense (Ohri et al, 2015). NPR1 also regulates the BR signaling genes, BIN2 and BZRI, which induces stress tolerance in plants (Divi et al, 2010).…”
Section: Brassinosteroids and Salicylic Acidmentioning
confidence: 99%
“…Besides that, they have also been attributed to the modulation of biotic and abiotic stress responses whereby crosstalks exist between the two networks (Ku et al, 2018). Under a stressful condition, antagonistic or synergistic crosstalks also happen between different phytohormones in plants (Ohri et al, 2015). Though complex, the crosstalks between phytohormone signaling cascades are deemed fundamental in fine-tuning the allocation of resources to the most appropriate defense mechanisms (Pieterse et al, 2012).…”
Section: The Production Of Soluble Sugars Krebs Cycle-associated Carmentioning
confidence: 99%
“…Plant hormones play an essential role in plant development, responses to environmental cues, and are central component in stress signaling pathways (Ohri et al., 2015; Sah et al., 2016; Ullah et al., 2018). Hormones enable the plant to perceive internal and external signals and adapt their development using complex signaling networks.…”
Section: Introductionmentioning
confidence: 99%